Deep Learning for Cognitive Computing Systems Technological Advancements and Applications - Sumithra, M. G.; Iwendi, Celestine; Kumar Dhanaraj, Rajesh; Merline Manoharan, Anto (De Gruyter, 2022)
Cognitive computing simulates human thought processes with self-learning algorithms that utilize data mining, pattern recognition, and natural language processing. The integration of deep learning improves the performance of Cognitive computing systems in many applications, helping in utilizing heterogeneous data sets and generating meaningful insights
Keywords: Big Data; Cognitive Computing; Deep Learning; Künstliche Intelligenz; Maschinelles Lernen